THE INFLUENCE OF THE IMPLEMENTATION OF PROJECT BASED LEARNING LEARNING MODEL USING CHEMOENTREPRENEURSHIP APPROACH ON THE LEARNING OUTCOME AND ENTREPRENEURSHIP INTEREST OF SMA NEGERI 1 SAMARINDA SCIENCE PROGRAM STUDENT ON COLLOIDAL SYSTEM TOPIC IN 2014/201 - Ratna Kusumawardani; Rexy Anderson Tindangen (PROSIDING SEMINAR KIMIA, 2015)
This research objective was to determine the influence of the implementation of Project Based Learning (PjBL) learning model with chemoentrepreneurship approach on the learning outcome and entrepreneurship interest of SMA Negeri 1 Samarinda student on colloidal system topic. The population was all eleventh grade students of SMA Negeri 1 Samarinda science program, meanwhile the sample was the eleventh grade students of 5th Science program class. This research used one shot pretest-posttest design, which only use 1 class as sample. The influence was determined by comparing the result of pretest and posttest and analyzed by using t test method, meanwhile the learning outcome and entrepreneurship interest improvement category were analyzed by using N-gain method. The results of the implementation of Project Based Learning (PjBL) learning model with chemoentrepreneurship approach showed a significant influence on the learning outcome and entrepreneurship interest of SMA Negeri 1 Samarinda student on colloidal system topic. According to N-gain test, the students’ learning outcome on first and second meeting has improved and the improvement is on medium category, meanwhile the students’ entrepreneurship interest also improved and the improvement is on low category.